Recent Trends and Developments in Bioinformatics: Challenges and Opportunities - (:unkn) unknown (My University, 2016)
Use of bioinformatics tools in life sciences have become necessary to analyze experimental data since omics have emerged in this field. The large amount of data is a challenge for the biological community as most biologists are not familiar to informatics and statistical interpretation and concepts. An interdisciplinary collaboration is welcome to explain to data analysts the needs of biologists, and to help biologists to understand their data. Here, we provide an opportunistic view of bioinformatics and its growth for various disciplines. Hundreds of tools, pipelines and applications have been developed to analyze this ample amount of biological data being generated on a daily basis at the global level. Galaxy is one such platform created in 2005 to allow scientists to analyze their data and share workflows in a reproducible, transparent, and accessible way to generate biologically meaningful information. With the consequential steps from NIH, EBI and other reputed institutions, several global initiatives have been proposed and implemented. One such initiative in Africa is H3ABionet, which is focusing on the development of Bioinformatics all over Africa and to connect African countries to the rest of the world technically.
Keywords: African Research